Aktivitas Antibakteri Gel Hand SanitizerMinyak Biji Pala (MyristicafragransHoutt) Terhadap Bakteri Gram Positif dan Gram Negatif - Agustin, Rachmawati Dwi; Taihuttu, Yuniasih Mulyani Jubeliene (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2024)
One of the media for spreading the bacteria the fastest in hand, so an antibacterial substance is needed. Hand sanitizers, which are more effective in killing bacteria, by quickly processing hands with airflow. However, most of the hand sanitizers' content is alcohol, which can repeatedly irritate the skin, so natural ingredients are needed to make hand sanitizers. Nutmeg is a tropical plant that is commonly found in Indonesia. Nutmeg contains active compounds as antibacterial agents. Research on the antibacterial activity test of the hand sanitizer gel formulation of nutmeg oil has been carried out. This study aimed to determine the antibacterial activity in the optimum formulation of the nutmeg oil hand sanitizer gel. Antibacterial activity test using the disc diffusion method showed that the nutmeg oil hand sanitizer gel had antibacterial activity against several pathogenic bacteria, including Escherichia coli, Staphylococcus aureus, Propionibacterium acne, and Pseudomonas aeruginosa, which were optimum concentration in nutmeg oil by 15% (F1), obtained the inhibition power of 1.42 mm; 1.35 mm; 0.56 mm; and 1.67 mm, respectively.